Investigating the relationship between sleep disturbances and psychopathology In children and adolescents with microdeletion of 22q11 chromosome: an exploratory study - Lala, Maria Rosaria; Bellantoni, Domenica; Montanaro, Federica Alice Maria; Pontillo, Maria; Alfieri, Paolo; Vicari, Stefano (Frontiers in Psychiatry, 2025)
Introduction22q11.2 deletion syndrome (22q11.2DS), also known as velo-cardiofacial syndrome or DiGeorge syndrome (DGS) is highly variable in phenotype, encompassing a wide range of physical and neuropsychiatric manifestations (ID, ADHD, ASD, anxiety, major depressive disorder,obsessive-compulsive disorder, schizophrenia). In this retrospective study, we aimed to assess the clinical significance of sleep disturbances and their relationship with functional impairment in a cohort of 52 children and adolescents with 22q11.2DS, as well as psychological distress in their parents. Standardized measures, including the Sleep Disturbance Scale for Children (SDSC) and the Parenting Stress Index-Short Form (PSI-SF), were administered to parents.MethodsThe sample consisted of 26 males and 26 females, aged 5 to 18 years. Participants were referred to the Day Hospital follow up of Child and Adolescent Neuropsychiatry Unit in the Bambino Gesù Children’s Hospital in Rome, Italy, between January 2023 and December 2023. The total cohort was divided into two main groups based on the presence of sleep problems: (1) Group 1, with sleep problems, and (2) Group 2, without sleep problems. Both groups demonstrated low mean IQ scores and low general adaptive functioning, as measured by the Wechsler Intelligence Scale for Children (WISC-IV) and the ABAS II General Adaptive Composite (GAC), respectively. Furthermore, Group 1 exhibited significantly lower functioning when assessed using the CGAS. Additionally, Group 1 reported higher levels of self-reported anxiety symptoms (MASC-2) compared to Group 2. While none of the results reached the clinical range, scores in Group 1 were generally higher, particularly on the “Performance Fears” subscale. A similar trend was observed in the “Negative Self-Esteem” subtest of the CDI 2 (self-report form). Although the average questionnaire scores did not fall within the clinical range, KSADS psychiatric diagnoses revealed the presence of various psychiatric disorders. Unexpectedly, these disorders were more prevalent in the group without sleep problems, except for anxiety disorders, which showed similar prevalence across both groups. Regarding parental stress, as measured by the PSI-SF, we did not observe a significant relationship between sleep disorders and parental stress, on the contrary to our expectations.Results and discussionOur study is one of the few to specifically investigate sleep problems in the pediatric population with 22q11.2DS and the first to use the Sleep Disturbance Scale for Children (SDSC) to assess various aspects of sleep disorders in this group. Further studies are required to draw more consistent conclusions.